Gender Gaps in Early Educational Achievement - Deborah A. Cobb-Clark; Julie Moschion (Institute for the Study of Labor (IZA), 2015)
This paper analyzes the source of the gender gap in third grade numeracy and reading. We adopt an Oaxaca-Blinder approach and decompose the gender gap in educational achievement into endowment and response components. Our estimation relies on unusually rich panel data from the Longitudinal Survey of Australian Children in which information on child development reported by parents and teachers is linked to each child's results on a national, standardized achievement test. We find that girls in low- and middle-SES families have an advantage in reading, while boys in high-SES families have an advantage in numeracy. Girls score higher on their third grade reading tests in large part because they were more ready for school at age four and had better teacher-assessed literacy skills in kindergarten. Boys' advantage in numeracy occurs because they achieve higher numeracy test scores than girls with the same education-related characteristics.
Keywords: J16; I21; I24; 330; education; educational achievement; gender gaps; Australia